2011
DOI: 10.1021/ja110541t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sensitizer Adsorption Temperature on the Performance of Dye-Sensitized Solar Cells

Abstract: Employing a mesoscopic titania photoanode whose bilayer structure was judiciously selected to fit the optoelectronic characteristics of the Ru-based heteroleptic complex Na-cis-Ru(4,4'-(5-hexyltiophen-2-yl)-2,2'-bipyridine)(4-carboxylic-acid-4'-carboxylate-2,2'-bipyridine)(thiocyanate)(2), coded as C101, we investigated the effect of temperature for dye adsorption on the photovoltaic performance of dye-sensitized solar cells (DSCs). We found a significant efficiency enhancement upon lowering the temperature ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(81 citation statements)
references
References 23 publications
4
77
0
Order By: Relevance
“…Furthermore, there is no proportionality between the efficiency, η, and Г dye (Table 1). This finding is supported by Sauvage et al [31] who reported on decreasing efficiency for the C101-sensitized films, if the Г dye was larger than the monolayer coverage. They concluded that subtle structural characteristics at the C101/TiO 2 interface influence the electron transfer dynamics and light harvesting of the assembly [31].…”
Section: Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, there is no proportionality between the efficiency, η, and Г dye (Table 1). This finding is supported by Sauvage et al [31] who reported on decreasing efficiency for the C101-sensitized films, if the Г dye was larger than the monolayer coverage. They concluded that subtle structural characteristics at the C101/TiO 2 interface influence the electron transfer dynamics and light harvesting of the assembly [31].…”
Section: Methodssupporting
confidence: 73%
“…The electrodes were soaked at room temperature in the solution overnight to secure complete attachment of the sensitizer dye to the electrode surface. To avoid irregularities in dye attachment [31], the sensitization time and temperature were identical for all the tested electrodes. The DSC was assembled with platinized F-doped tin oxide (FTO) counter electrode [32,33] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.0% Ga the -conjugation in the ancillary ligand not only exerts an energetic stabilization of the LUMO levels, thus redshifting the dye absorption, but also favorably affects the molar extinction coefficient of the dye reaching more than 20000 M −1 ⋅cm −1 [12,15,[112][113][114][115]. The integration of this second generation of dyes paved the way to improved performances in terms of light harvesting and power conversion efficiency.…”
Section: Dye-sensitized Solar Cells Principle: Role and Progress In Tmentioning
confidence: 99%
“…Rapidly passing the threshold of 10% power conversion efficiency (PCE) in 1993 [10], despite endless efforts on material development, the efficiency had stagnated for a long time in the range of 11.0-11.5% [11][12][13][14][15][16] before scoring three new subsequent records, first 12.3% and 13.0% under A.M. 1.5 G conditions (100 mW/cm 2 ) using organic dye molecules in association with a stronger oxidant redox active cobalt polypyridyl complex [17,18]. More recently, certified 14.1% and even certified 17.9% PCE have been achieved by replacing the dye with a hybrid organic/inorganic lead halide perovskite absorber and the liquid electrolyte by a solid hole transporting material (HTM) [19,20] giving birth to a new technology called perovskite solar cells, for which progresses are remarkably fast.…”
Section: Introductionmentioning
confidence: 99%